Analisis Budaya Dalam Film Karate Kid (2010) dan Perannya Dalam Pembelajaran Cross Culture Understanding - Audryan Avia Putra (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2023)
This research aims to analyze cultural types in the movie "Karate Kid (2010)" and its role in Cross Culture Understanding learning. The objectives of this research are: 1) To discover the cultural types present in the movie "Karate Kid (2010)". 2) To find out the contribution of cultural types in the movie "Karate Kid (2010)" to teaching Cross Culture Understanding. The researcher uses a descriptive qualitative method, which is a qualitative research method. The movie "Karate Kid (2010)" is the main object of this analysis. The techniques involve watching the movie several times to thoroughly understand the subject, analyzing the data, collecting data to classify it of cultural types, and then interpreting the data. In the process of analysis, the researcher found cultural types in the movie "Karate Kid (2010)" including art, buildings, transportation, food, language, beliefs, and oral traditions. Based on this analysis, the researcher found that cultural types can be used to teach Cross Culture Understanding. The movie "Karate Kid (2010)" is presented as an alternative learning material in Cross Culture Understanding, and this research can be used as a source for teaching Cross-cultural understanding.